AKTIVITAS PENANGKAP RADIKAL BEBAS DARI EKSTRAK FENOLIK DAUN SUKUN (Artocarpus altilis F.) - Suryanto, Edi; Wehantouw, Frenly (Sam Ratulangi University, 2009)
The objectives of this study was to determine phytochemicals content and free radical scavengingactivities of bread fruit leaves. Bread fruit leaves were finely ground in a laboratory mill and samples wasextracted with methanol, ethanol and acetone under room temperature, respectively. Analyses ofphytochemicals based on total phenolic, flavonoid and condensed tannins. The radical scavengingactivities of extracts were determined by 1.1-diphenyl-2-picrylhydrazyl (DPPH) and the ferric reducingability plasma assay. The highest total phenolic content was in methanol extract (EM), followed byethanol extract (EE) and acetone extract are 179.89 ± 3.17; 152.55 ± 3.17 and 62.46 ± 1.31 mg/Kgrespectively. EM possessed highest contents of total flavonoid and condensed tannins compared with EEand EA. The addition of methanol extracts of in the reaction mixture showed the highest scavengingactivity in 1.1-diphenyl-2-picrylhydrazyl (DPPH) radical 74.80% followed by EE 71.80% and 38.80%.These result suggested that contains phenolic compounds groups having free radical scavengingactivities.